Assessing COVID-19 vaccine literacy: a preliminary online survey - Luigi Roberto Biasio; Guglielmo Bonaccorsi; Chiara Lorini; Sergio Pecorelli (Taylor & Francis Group, 2021)
The COVID-19 infodemic can be countered by scientific evidence, clear and consistent communication, and improved health literacy of both individuals in need of information and those providing it. A rapid online survey was carried out to evaluate vaccine literacy (VL) skills in the general population and perceptions about COVID-19 vaccine candidates, along with behavior and beliefs about current vaccinations. Observed VL levels were consistent with previous observations - where comparable self-reported tools were administered face-to-face and by paper-and-pencil - the mean functional score being = 2.92, while the interactive-critical score was = 3.27, out of a maximum of 4. Perceptions regarding future COVID-19 vaccines, along with beliefs about vaccination, were mostly positive and significantly associated with functional and interactive-critical VL scales. Despite limitations, the study confirms that surveys via the web are a suitable method to evaluate and track attitudes during infectious disease outbreaks and assess health literacy skills about vaccination, which can be useful to adapt medical communication strategies, for a better understanding of the value of immunization.